Joaquín García Monge’s La Edad de Oro: A selection and edition of universal and Latin American readings - Rodríguez-Vargas, Nuria (2023)
During the 1920’s, the Costa Rican writer Joaquín García Monge -inspired by La Edad de Oro (The Golden Age) of José Martí- edited a great selectionof Latin American and universal texts based on different subjects and genres. He intended to connect with students belonging to the public education system. At the beginning, texts were published in Repertorio Americano, and then as a Supplement to this magazine, in 160-page notebooks. The aim of this article is to make a general description of the contents of the six volumes that became to be published and, at the same time, to highlight the influence of Martí on García Monge.